Communication Network of Women Vegetable Growers of Nainital District of Uttarakhand (Indian Journal of Extension Education, 2017)
Acommunication network consists of interconnected individuals who are linked by a patterned exchange of information. Its analysis identifies the communication structure in a system. Exchange of information and its diffusion takes place within a social system and the roles of actors such as people and organizations affect the diffusion of the innovation process. The present study was undertaken to delineate the communication network of women vegetable growers of Nainital district of Uttarakhand state. The study was conducted in six randomly selected villages of Community Development Blocks namely, Haldwani, Ramnagar and Dhari in Nainital district during 2012-2014. The approach of sociometry was applied to probe the key communicators in dissemination of vegetable related information. The respondents were asked from whom they seek advice or suggestion in matters related to vegetable cultivation .Their responses were noted and key communicators were identified and diagrammatically depicted using target sociogram technique. Communication stars of each village were identified from the sample respondents. Results of the study emphasized on capacity building programme for communication stars to promote vegetable cultivation.